Formación docente universitario en el uso de las tic para mejorar la práctica pedagógica - Blanca Mery Rolón Rodríguez; Jorge Enrique Herrera Rubio; Francisco Flores Cuevas (Mundo Fesc)
This research is the result of a study carried out at the University of Pamplona, ​​Colombia, during the pandemic. It focused on teacher training processes and aimed to analyze pedagogical practices through the use of information and communication technologies (ICTs) as teaching strategies to reduce low academic achievement. The descriptive correlational study was based on quantitative methods with a qualitative interpretation; the sample included 125 teachers from the higher education institution, who answered a 120-question questionnaire through which the proposed variables were measured using descriptive statistics. From the results obtained it was established that most of the teachers surveyed, in relation to pedagogical and epistemological training, there is evidence of a need for greater mastery in other pedagogical models of teaching-learning with innovative strategies, which is reflected in the low participation of students in classes and therefore in the demotivation and low performance of students in the Faculty of Education, thus concluding on the importance of adopting emerging pedagogies such as e-learning for the proper development of classes.